Mulching impact of Jatropha curcas L. leaves on soil fertility and yield of wheat under water stress - Irshad, Muhammad; Ullah, Faizan; Mehmood, Sultan; Al-Huqail, Asma A; Fahad, Shah; Siddiqui, Manzer H; Ali, Hayssam M; Saud, Shah; Danish, Subhan; Datta, Rahul; Dawar, Khadim (Scientific reports, 2022)
In present studies we have evaluated mulching impact of Jatropha curcas leaves on soil health and yield of two wheat (Triticum aestivum L.) varieties Wadan-2017 (rainfed) and Pirsabak-2013 (irrigated) under imposed water stress. Mulch of Jatropha leaves was spread on the soil surface at the rate of 0, 1, 3 and 5 Mg ha-1 after seed germination of wheat. Water stress was imposed by skipping irrigations for one month at anthesis stage of wheat maintaining 40% soil field capacity. We found a significant decline in soil microbial biomass carbon (30.27%), total nitrogen (22.28%) and organic matter content (21.73%) due to imposed water stress in non-mulch plots. However, mulch application at 5 Mg ha-1 significantly improved soil organic matter (38.18%), total nitrogen (37.75%), phenolics content (16.95 mg gallic acid equivalents/g) and soil microbial biomass carbon (26.66%) as compared to non-mulch control. Soil health indicators like soil carbonates, bicarbonates, electrical conductivity, chloride ions and total dissolved salts were decreased by 5 Mg ha-1 mulch application. We noted a decline in yield indicators like spike weight (14.74%), grain spike-1 (7.02%), grain length (3.79%), grain width (3.16%), 1000 grains weight (6.10%), Awn length (9.21%), straw weight (23.53%) and total grain yield (5.98%) of wheat due to imposed water stress. Reduction in yield traits of wheat due to water stress was higher in Pirsabak-2013 than Wadan-2017. Jatropha leaves mulch application at 5 Mg ha-1 significantly minimized the loss in yield traits of wheat crop caused by water stress. Jatropha curcas leaves mulch application at 5 Mg ha-1 is recommended for the successful establishment of wheat crop under water deficit conditions.
Keywords: dusík; listy rostlin; zemědělství; uhlík; Agriculture; Soil; Triticum; pšenice; půda; Dehydration; dehydratace; Jatropha; Carbon; Nitrogen; Plant Leaves